Stress Sources and Manifestations in a Nationwide Sample of Pre-Primary, Primary, and Secondary Educators in Greece - Kourmousi, Ntina; Alexopoulos, Evangelos C. (Frontiers in Public Health, 2016)
Background Teachers experience high levels of stress as a result of their professional duties and research has shown a growing interest in this phenomenon during the recent years. Aim of this study was to explore the associations of stress sources and manifestations with individual and job-related characteristics in educators of all levels. Methods In a cross–sectional design, following an informative e-campaign on the study aims through the official and the main teachers’ portals in Greece, respondents completed online the Teachers Stress Inventory (TSI) and the 14-item Perceived Stress Scale (PSS-14). 974 male and 2473 female pre-primary, primary and secondary educators with a mean age of 41.2 years responded. Results Women and younger teachers reported significantly higher levels of stress, mainly due to lack of time and other work-related stressors, and also more emotional and gastronomic manifestations. Increased age and working experience were associated with lower levels of several stress sources. Teachers of administrative positions had increased time management stressors, but less professional distress, professional investment and discipline and motivation stressors. Additionally, working and residing far from family increased teachers’ stress levels associated to control, motivation and investment. Teachers of pre-primary education had reduced professional investment and motivation stress factors while vocational lyceum teachers of secondary education reported less work-related stressors and manifestations and more discipline and motivation related ones. Having students supported or in need of support from special educators and students with difficulties in speaking or comprehension was associated with most of the teachers' stress sources and manifestations (i.e. TSI subscales). Finally, colleagues’ and mainly supervisors' support seemed to provide a strong and consistent protection against both stress sources and manifestations. Conclusions Stress factors and manifestations vary among educators by gender, seniority and educational level. Training in coping and communication skills starting in teachers’ undergraduate studies might have a major impact on their stress alleviation.